Aktifitas Dakwah Keagaman Ahlul Bait Nabi di Wilayah Lampung (1998-2014) - Muhamad Bisri Mustofa; Wahyu Iryana; Siti Wuryan (Ath Thariq Jurnal Dakwah dan Komunikasi, 2023)
Research related to religious activities carried out by habaib located in the South Sumatra Region, more precisely in Lampung and its role in Islamic proselytizing in the period 1998 to 2014. The majority of habaib in the archipelago are predominantly from Hadralmaut and are quite large in spread, while this research is more specifically only discussing habaib in the Lampung region. This research was conducted to find out the history of the entry of habaib in Lampung as well as habaib religious activities in Lampung which of course have a variety of activities to broadcast Islamic proselytizing, as well as strengthen the Islamic community in Lampung. The research method used by the author is a historical research method, which is research that studie past events or events based on the traces produced, through four stages, namely: heuristics (collection of sources), criticism (internal criticism and external criticism), interpretation, and historiography (historical writing). Based on the research, it can be concluded that: first, this habaib community came from Hadhramaut (Yemen) in the 18th century. Initially, the habaib community in Lampung was still classified as an Arab community in Palembang, but in 1872 the Lampung community broke away from the Palembang Arab community, and spread throughout the area in Lampung. Although the Arab-Lampung community is younger than the Palembang Arab community, Secondly, this habaib community carries out religious activities in Lampung consisting of weekly, monthly and yearly activities As for the religious activities of the habaib community that are carried out per week are the reading of Rattibul Hadad, and the reading of 40 shalawat, then the monthly habaib religious activities, which contain the reading of the history of the Apostle, and the Dhikr Asmaul Husna. The last is the religious activity per year habaib, which is carried out at the Lampung sports center which is held every November to coincide with the anniversary of Lampung Regency.